Energy Levels, Radiative Data and Collisional Excitation of Chlorine like Tungsten W\(^{57+}\) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2021)
Extended computation of energy levels and radiative data such as transition wavelengths, transition probabilities, and oscillator strengths for electric dipole (E1) transitions are performed for chlorine-like Tungsten ions WLVIII using the fully relativistic Flexible Atomic Code (FAC). Comparisons are done with the accessible experimental results and theoretical data in the literature. Close agreement has been found ensuring the accuracy and reliability of our results. We have studied collisional excitation cross section and presented magnetic sublevel cross sections for excitations from the ground state 3s\({}^{2}\) 3p\({}^{52}\)P\({}^{o}\)\({}_{3/2}\) to the first excited state 3s\({}^{2}\)3p\({}^{4}\)3d \({}^{4}\)D\({}_{3/2}\) of W\({}^{57+}\) as a function of incident electron energy. We calculate new data for several levels where no other theoretical and/or experimental results are available. Our work will help to develop diagnostics for evaluating tungsten concentrations in fusion plasmas and provide platform for modeling predictions.
Keywords: Transition probabilities; Oscillator strengths; Excitation cross section